MORAL EDUCATION IN ELT: A CRITICAL DISCOURSE ANALYSIS OF TOLERANCE VALUES REPRESENTED IN INDONESIAN EFL TEXTBOOK - Filzah Khoirunisa; Maman Suryaman; Elih Sutisna Yanto (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
This present study investigates the representation of tolerance values in cultural and religious difference in EFL textbook approved by Ministry of Education and Culture (MONEC). The study used critical discourse analysis to investigate both visually and verbally text that represent tolerance values in the ELT textbook for Junior High School grade VII entitled “Bahasa Inggris: When English Rings a Bell”. The data was analyzed by  using the Miles, Huberman, & Saldana’s (2016) model that consisted of data identification, data reduction, data display, conclusion drawing, and verification. The finding shows that textbook contains the tolerance values in cultural and religious difference. The other finding indicates that tolerance values are mostly predominantly depicted in the textbook through activity with fellow students or peers such as behaving politely to elder, caring to peers and respect to others habitual action without distinguish between religion and ethnic culture. It was suggested that language textbook designers need to be fully aware of tolerance values and tolerance sensitivity when writing language textbook. This is because language textbook teach not merely linguistics and communicative competence/skills but also knowledge and deliver the moral messages. Keywords: Critical discourse analysis, English textbook, moral education, tolerance values